ANALISA KINERJA KARYAWAN PT. PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA DITINJAU DARI PERAN PELATIHAN KERJA DAN PENGEMBANGAN KARIR - Lyta Karina; Handoyo Djoko Waluyo (Jurnal Ilmu Administrasi Bisnis, 2017)
Human resource is a valuable asset for performance’s organization and because employees work and act dedicated for the achievement of organization’s goals through good performance. Employee performance improvement will bring progress for the company to survive in a global competitive business environment. The purpose of this research is to discover the effect of job training and career development toward employee performance in PT. PLN (Persero) Central Java & Special District of Yogyakarta Region. The type of research is explanatory research. The sampling technique is using Proportionate Stratified Random Sampling method. The total of samples was 136 respondents. Computer programs SPSS 22.0 is used for data processing in this research. Based on the results of descriptive analysis, 60,3 percent indicates that variable job training is in quite well category. Then, 58,1 percent indicates that variable career development is in quite well category too and variable employee performance is in the high category, amounting to 50,0 percent. Based on the multiple correlation coefficient calculation, it shows value 0,815 which means the variables have a strong correlation. Based on the calculation of the determination coefficient it indicates that the variable in this research which is job training and career development contributed as much as 66,4% for employee performance. Suggestions in this research are to conduct perform a thorough evaluation to every employee after training. PT. PLN (Persero) could utilize Kirkpatrick’s four level evaluation training programs in reactions and learning level. Adjustment between trainees learning style with the trainee is also very necessary. In addition, more proactive action is needed from the mentors to share knowledge in the context of career development of employees in the company in order to achieve better common goals.